A Scoping Review of School-Based Mental Health Measurement in Adolescents - Tri Rejeki Andayani; Farida Hidayati (Universitas Muhammadiyah Surakarta, 2026)
Adolescent mental health, particularly depression, anxiety, and stress, has a high prevalence and significant impact on their development. Schools, as environments where most adolescents spend a considerable amount of time, hold significant potential in supporting their mental health. However, the availability of valid and effective measurement tools for assessing adolescent mental health in school settings remains limited. This study aims to identify the measurement tools used in school-based research for assessing adolescent mental health, as well as the approaches to data collection and interpretation. The review follows the PRISMA protocol and adopts Arksey and O'Malley’s methodology, including a comprehensive literature search across various databases and selection of articles that meet predefined inclusion criteria. A total of 1441 articles were identified, and 26 met the inclusion criteria for analysis. The results indicate that the most frequently used tools for measuring depression, anxiety, and stress in adolescents are the DASS-21, PHQ-9, CES-DC, GAD-7, and DQ5 with most studies utilizing Likert scales for assessments. Data collection was primarily self-reported by adolescents, with variations in questionnaire administration duration and measurement timeframes, and generally good internal consistency. These findings underscore the importance of selecting appropriate and reliable measurement tools to obtain valid and accurate data on adolescent mental health. The review offers critical insights for the development of more effective tools to support school-based mental health interventions